A classe trabalhadora condenada por tráfico de drogas: um estudo das mulheres em execução penal na Comarca de Cascavel/PR a partir da Lei nº 11.343/2006 - Oliveira, Vívian Bertelli Ferreira de (2016)
Drugs are a very current and controversial issue, where the company builds its concepts and prejudices and them makes uses for construction of social insecurity, attributing to drugs, particularly illicit, and its users and producers responsibility for alleged "social evils". I assume that drugs are goods for capitalist society and, as commodities, they have a production process that involves the work process, with the means of production (raw materials and work tools) and workforce and the process of valuation of goods, with circulation, distribution and consumption. Therefore, the process of drug commodity production has its workers, who are called, pejoratively, drug traffickers and punished by society, and capitalists of drugs, those who own the means of production and put into circulation the goods / produced drugs and still appropriate the large amounts produced, but that are not socially recognized as traffickers or as criminals. We have as object of research the working class convicted of drug trafficking as a strategy of social control. And in that sense, we put the following research problem: to what extent the conviction of women for drug trafficking responds to the interests of capitalist society? It is thinking about the prohibition of the impacts of certain drugs and the meaning of this portion control policy of the population we set out to analyze the concept of drugs, their uses and customs, as well as uncover the selectivity of the penal system from the Law number 11.343/2006 and present the reality of western Paraná, from field research that identified the criminal Executions Court of Rattlesnake County 822 people related to drug trafficking crime, in the aforementioned law. Since these people 120 were female, cut the questioning of this research, and representing 62% of women in criminal enforcement of the District. From this, unveil the profile of these women, their relationships with the Paraná prison public and Brazil, as well as the 143 criminal actions of these women and we completed this work with a case report by checking the materiality of social control fractions of the working class .